2020
DOI: 10.3390/antiox10010041
|View full text |Cite
|
Sign up to set email alerts
|

Insight Study on the Comparison between Zinc Oxide Nanoparticles and Its Bulk Impact on Reproductive Performance, Antioxidant Levels, Gene Expression, and Histopathology of Testes in Male Rats

Abstract: Background: Despite the beneficial effects of zinc oxide nanoparticles (ZnONPs) on different biomedical applications, including their antioxidant and anti-inflammatory ones, it might have cytotoxic and genotoxic impacts on the male reproductive system. Objective: The current study compares the effect of zinc oxide nanoparticles and their bulk form, at different doses, on male rats’ reproductive performance, testicular antioxidants, gene expression, and histopathology. Materials and Methods: Thirty male rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…This is due to their high redox activity and antioxidant properties shown in Wistar rats (Nikitchenko et al, 2021a;2021b). Similar results have been reported by researchers using alternative antioxidant therapies for male infertility, such as NPs of zinc oxide, melatotin or coenzyme Q 10 (Banihani, 2018;Obembe, 2019;Goma et al, 2020;Zhao et al, 2021).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This is due to their high redox activity and antioxidant properties shown in Wistar rats (Nikitchenko et al, 2021a;2021b). Similar results have been reported by researchers using alternative antioxidant therapies for male infertility, such as NPs of zinc oxide, melatotin or coenzyme Q 10 (Banihani, 2018;Obembe, 2019;Goma et al, 2020;Zhao et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…Thus, with the administration of NPs based on gold, silver and molybdenum, which are widely used in medical practice, the initiation of OS in gonads and pathological effect on their structural organization are observed. Instead, zinc oxide NPs caused an increase in sperm quality, sex hormone content and normalization of antioxidant potential (Asadi et al, 2017;Barati et al, 2020;Goma et al, 2020;Liu et al, 2020;Olugbodi et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Patron-Romero et al (Patron-Romero et al 2020) exposed C2C12 mouse broblasts, L929 myoblasts and HLPB human peripheral blood lymphocytes to 20-30 µg/L ZnO-NPs with particle sizes of 16-24 nm for 6 h, 12 h, and 24 h, after which the cells exhibited varying degrees of DNA damage accompanied by severe cell death. Goma et al (Goma et al 2021) found that 50 nm ZnO-NPs induced oxidative stress damage in male rats, which triggered an in ammatory response. ZnO-NPs induced in ammatory and apoptosis in the lung cells of female mice (Rossner et al 2019).…”
Section: Introductionmentioning
confidence: 99%